2020
DOI: 10.3390/ijerph17218131
|View full text |Cite
|
Sign up to set email alerts
|

Total Diet Study to Assess Radioactive Cs and 40K Levels in the Japanese Population before and after the Fukushima Daiichi Nuclear Power Plant Accident

Abstract: We conducted a total diet study (TDS) of 137Cs, 134Cs, and 40K to assess their average dietary exposure levels in a Japanese adult population before and after the Fukushima Daiichi nuclear power plant (FDNPP) accident. Nineteen market baskets were evaluated in 2006–2011. In each basket, a TDS sample comprising tap water and 160–170 food items, which were combined into 13 groups, were collected for analysis by gamma-ray spectrometry. From 2006 to 2010, the 137Cs activity concentration in the “fish and shellfish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This survey shows the average food intake (g/day) classified into 98 small categories of foodstuffs ( Table 2 ) [ 19 ]. The average food intake value is typically used in radiation dose estimation studies of internal exposure due to food ingestion [ 20 ], including in our previous reports [ 16 , 17 ]. However, radiation dose estimation based on average food intake might underestimate internal doses for people with high intake.…”
Section: Methodsmentioning
confidence: 99%
“…This survey shows the average food intake (g/day) classified into 98 small categories of foodstuffs ( Table 2 ) [ 19 ]. The average food intake value is typically used in radiation dose estimation studies of internal exposure due to food ingestion [ 20 ], including in our previous reports [ 16 , 17 ]. However, radiation dose estimation based on average food intake might underestimate internal doses for people with high intake.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the monitoring of 134,137 Cs in organisms may need to continue until they decay naturally or dissipate in the environment to undetectable levels [4][5][6][7][8][9][10][11]. The processes of the resuspension of 134,137 Cs are not fully understood but many studies have concluded that the concentrations and exposure levels of radioactive Cs were well below regulatory levels, and that their contribution to the long-term exposure of the public from consuming foodstuffs has not been significant in recent years [12][13][14].…”
Section: Introductionmentioning
confidence: 99%